A register analysis of exhibition texts at Islamic Arts Museum Malaysia - Ummu Zainab Al-Abidah binti Zainal Abidin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Exhibition texts are commonly found alongside exhibitions in a museum. It is often assumed that these texts are there to serve specific purposes in the overall context of the museum. As such, one of the ways in which the purposes of a museum may be examined is through the study of its exhibition texts and their relationship with the museum's particular context. This study examines the context of Islamic Arts Museum Malaysia and its exhibition texts with the aim of identifying the characteristics of the museum context, finding out the frequency and pervasiveness of selected linguistic features in the exhibition texts and evaluating how the characteristics of the museum context are reflected in the use of these linguistic features. Register Analysis framework of Biber and Conrad (2009) was used for analysing the museum's characteristics, linguistic features in the exhibition texts and functional interpretation of the texts. The findings of the study reveal that the museum unique characteristics are reflected in the use of the linguistic features found in the exhibition texts, confirming the view of register study which states that language is functional and serves the purposes of the texts in its context. The thesis concludes that museum exhibition texts are significant in enabling the museum to function as a public and educational institution.